Electricity planning - utilization of biomass for electricity generation - Zarina A. M. (Forest Research Institute Malaysia, 2014)
Electricity generation industry in Malaysia mostly relies on conventional sources of fuel i.e. coal, natural gas, diesel and fuel oil. Natural gas and coal constitute 66% and 23.3% of the total electricity generation respectively. In the 9th Malaysia Plan, the government has encouraged power producers to shift towards alternative energy including biomass, solar and nuclear to reduce the reliance on natural gas and other types of fossil fuels. In this study, a Mixed Integer Linear Programming (MILP) model has been developed to optimize fuel mix and meet the CO2 emission target. The model was developed and implemented in General Algebraic Modeling System (GAMS) for the fleet of electricity generation in Peninsular Malaysia. In order to reduce the CO2 emissions by 40% from current CO2 emission level, the optimiser has specified to adapt Natural Gas Combined Cycle (NGCC), hydro and biomass from palm oil residues and rice processing residues. It was also found that Malaysia can generate up to 9% of electricity supply from biomass residues.